ARTIFICIAL PNEUMOPERITONEUM IN DESTRUCTIVE PULMONARY TUBERCULOSIS AS AN ADJUNCT TO PULMONARY SURGERY - B.U. SALIKHOV; E.V. KRASNIKOVA; V.K. ALIEV; R.V. TARASOV; N.L. KARPINA; M.A. BAGIROV (Паёми Сино)
Objective: To evaluate the effectiveness of artificial pneumoperitoneum (APP) during the perioperative period in patients with destructive pulmonary tuberculosis (PT) who require pneumonectomy (PE) with anterior mediastinal plasty (AMP).